Antidiabetic Activity Of Phaleria Macrocarpa (Scheff.) Boerl Fruit Extracts - Ali Antisha, Rabyah B. (2012)
The fruit of Phaleria macrocarpa is used in traditional medicine in Indonesia and the eastern part of Malaysia, as a remedy for the management of diabetes mellitus. This study was therefore carried out to investigate the antidiabetic activity of this fruit in normal and streptozotocin (STZ) -induced diabetic rats. The pulverized dried fruits were sequentially extracted in petroleum ether, methanol and water. None of the extracts (1 g/kg) exerted an effect on blood glucose of normal rats. The methanol and water extracts significantly inhibited the rise of blood glucose after glucose loading in intra-peritoneal glucose tolerance tests (IPGTT) in normal rats.